DNA : the thread of life - Wilcox, Frank H. (Minneapolis : Lerner, 1988)
Presents the most recent information on the way in which DNA controls the operations of cells, using models and comparisons to familiar information systems.
Includes index.
School Library Journal.
7.3
7.3
5-8.
5-8
Keywords: DNA -- Juvenile literature; Genetics -- Juvenile literature; DNA; Genetics; DNA; Genetics